Health Polytechnic Lecturers’ Common Errors in Structure and Written Expression Tests - Purinanda, Faza Hannan; Nurhadianti, Sefi; Trisurini, Andika (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
The opening of international classes in several Health Polytechnics of Ministry of Health brings about direct and indirect ramifications. One of them is the increasing demand for English competency among the lecturers, as shown by their TOEFL ITP scores. In this regard, Structure and Written Expression is deemed the most difficult section of the test, hindering the attainment of the required scores. Therefore, this study attempts to find out the difficulties faced by the lecturers of a Health Polytechnic of Ministry of Health in answering the Structure and Written Expression questions. This is a basic qualitative study, employing error analysis as the main approach to examine the questions and lecturers’ answers in TOEFL ITP preparation programs. The results show that there are still difficulties in sentences containing dependent clauses as well as noun and verb phrases. Also, Written Expression questions are deemed more difficult than those of Structure.